How do People look at Pictures of Pigs? Analyzing Fixation Duration Depending on Pig Expression and Barn Type using Eye-Tracking - Sarah Gauly; Gesa Busch; Achim Spiller; Ulrich Enneking; Susanne Kunde; Marie von Meyer-Hof̈er (German Journal of Agricultural Economics (GJAE), 2020)
Using eye-tracking, this study investigates fixation duration of students viewing pictures of pigs, which systematically vary in the facial expression of the pig and in the barn setting. The aim of this study is to analyze which picture elements are viewed and for how long, as well as how fixation times vary with a change of the expression of the pig and the barn type. The results show clear effects of picture composition: pig expression and pen type affect fixation durations of different areas of interest with the influence of the pig being considerably larger. Face regions are viewed longer in the "happy" pig, while floor/bedding and the eyes are viewed longer in pictures showing the "unhappy" pig which might be a hint for information search. The power of facial expressions, also for the depiction of farm animals, is a new finding of this paper, which might be of importance when selecting agricultural pictures for different purposes.
Keywords: 330